Kesetaraan Gender dalam Akses Pendidikan di Pendidikan Tinggi: Sebuah Kajian Studi Fenomenologi: Penelitian - Rachmat Setiawan; Hasanudin; Endang Komara; Nandang Komara; Helmawati (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The background of this research is the issue of gender inequality that occurs in society resulting in different views on the roles of men and women. There is also the status of women in social life in many ways still experience discrimination with the still strong traditional values ​​​​where women have less access to one of them is access to education. The purpose of this study is to explain the understanding of gender equality in access to education, especially access to education to the higher education level. The method used is a qualitative method with stages namely observation, interviews, and literature studies. The results of this mini-research can increase understanding of gender equality in education and can realize and implement gender equality and justice in the scope of education in higher education. This research is interesting because in 2025 gender issues are still an iceberg phenomenon and similar research is still lacking.